To Mask or Not to Mask-Evaluation of Cognitive Performance in Children Wearing Face Masks during School Lessons (MasKids) - Anne Schlegtendal; Lynn Eitner; Michael Falkenstein; Anna Hoffmann; Thomas Lücke; Kathrin Sinningen; Folke Brinkmann (MDPI AG, 2022)
In the current SARS-CoV-2 pandemic, wearing a face mask is mandatory again during school lessons. There are no controlled studies in children to date indicating an effect on cognitive performance from wearing face masks. In a randomized controlled trial, we analysed the influence of face masks on cognitive performance of pupils during regular school lessons. Pupils (n = 133, fifth to seventh grade) were randomized by alternating allocation into control (with masks, n = 65) and intervention groups (without mask, n = 68). After two school lessons with (control) and without (intervention) face masks in class, all pupils performed digital tests for cognitive performance regarding attention and executive functions (switch, Corsi block-tapping, 2-back and flanker task). Overall, there were no significant differences in cognitive performance between both groups, masks vs. no masks. Wearing face masks has no significant influence on attention and executive functions of pupils and can still be recommended during school lessons.